1987
DOI: 10.1021/j100288a036
|View full text |Cite
|
Sign up to set email alerts
|

Stopped-flow studies of the mechanisms of ozone-alkene reactions in the gas phase: tetramethylethylene

Abstract: CH3)C(=0)CH2' radical as well as the accompanying HO' radical was formed in the 03-TME system via reaction 5.To further examine the oxidation of CH3C(=0)CH2' radicals, the photolysis of mixtures containing parts-per-million concentrations of Cl2 and (CH3)2C=0 in air yielded methylglyoxal H3C(=0)CH0 as a major product, i.e., ca. 30% of A-[(CH3)2C=0], which can be attributed to the oxidation of the CH3C(=0)CH2' radical. Thus, the observation of CH3C(= OjCHO in the 03-TME-02 system (cf. Tables I and II) is consis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
66
1

Year Published

1990
1990
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(72 citation statements)
references
References 5 publications
5
66
1
Order By: Relevance
“…This is likely to be a significant atmospheric sink for syn-SCIs because of their slow reaction with water vapour. Previous studies have identified the hydroperoxide rearrangement as dominant for SCIs with a syn configuration, determining their overall unimolecular decomposition rate (Niki et al, 1987;Rickard et al, 1999;Martinez and Herron, 1987;Johnson and Marston, 2008). This route has been shown to be a substantial non-photolytic source of atmospheric oxidants (Niki et al, 1987;Alam et al, 2013).…”
Section: Stabilised Criegee Intermediate Kineticsmentioning
confidence: 99%
“…This is likely to be a significant atmospheric sink for syn-SCIs because of their slow reaction with water vapour. Previous studies have identified the hydroperoxide rearrangement as dominant for SCIs with a syn configuration, determining their overall unimolecular decomposition rate (Niki et al, 1987;Rickard et al, 1999;Martinez and Herron, 1987;Johnson and Marston, 2008). This route has been shown to be a substantial non-photolytic source of atmospheric oxidants (Niki et al, 1987;Alam et al, 2013).…”
Section: Stabilised Criegee Intermediate Kineticsmentioning
confidence: 99%
“…Previous studies have identified the hydroperoxide rearrangement as dominant for SCIs with a syn configuration, determining their overall unimolecular decomposition rate (Niki et al, 1987;Rickard et al, 1999;Martinez and Herron, 1987;Johnson and Marston, 2008). This route has been shown to be a substantial non-photolytic source of atmospheric oxidants (Niki et al, 1987;Alam et al, 2013).…”
Section: Stabilised Criegee Intermediate Kineticsmentioning
confidence: 99%
“…. Unimolecular reactions of syn-CI/-SCIs are dominated by a 1,4-H shift, forming a vinyl hydroperoxide (VHP) intermediate (Niki et al, 1987;Rickard et al, 1999;Martinez and Herron, 1987;Johnson and Marston, 2008;Kidwell et al, 2016). Decomposition of the VHP formed in this process is an important non-photolytic source of OH, HO 2 and RO 2 in the atmosphere (Niki et al, 1987;Alam et al, 2013;Kidwell et al, 2016), which can also lead to secondary organic aerosol formation (Ehn et al, 2014).…”
Section: Stabilised Criegee Intermediate Kineticsmentioning
confidence: 99%